Quantification of transient increase of the blood–brain barrier permeability to macromolecules by optimized focused ultrasound combined with microbubbles - Shi L (Dove Medical Press, 2014)
Lingyan Shi,1 Paolo Palacio-Mancheno,1 Joseph Badami,2 Da Wi Shin,1 Min Zeng,1 Luis Cardoso,1 Raymond Tu,2 Bingmei M Fu11Department of Biomedical Engineering, 2Department of Chemical Engineering, The City College of the City University of New York, New York, NY, USAAbstract: Radioimmunotherapy using a radiolabeled monoclonal antibody that targets tumor cells has been shown to be efficient for the treatment of many malignant cancers, with reduced side effects. However, the blood–brain barrier (BBB) inhibits the transport of intravenous antibodies to tumors in the brain. Recent studies have demonstrated that focused ultrasound (FUS) combined with microbubbles (MBs) is a promising method to transiently disrupt the BBB for the drug delivery to the central nervous system. To find the optimal FUS and MBs that can induce reversible increase in the BBB permeability, we employed minimally invasive multiphoton microscopy to quantify the BBB permeability to dextran-155 kDa with similar molecular weight to an antibody by applying different doses of FUS in the presence of MBs with an optimal size and concentration. The cerebral microcirculation was observed through a section of frontoparietal bone thinned with a micro-grinder. About 5 minutes after applying the FUS on the thinned skull in the presence of MBs for 1 minute, TRITC (tetramethylrhodamine isothiocyanate)-dextran-155 kDa in 1% bovine serum albumin in mammalian Ringer’s solution was injected into the cerebral circulation via the ipsilateral carotid artery by a syringe pump. Simultaneously, the temporal images were collected from the brain parenchyma ~100–200 µm below the pia mater. Permeability was determined from the rate of tissue solute accumulation around individual microvessels. After several trials, we found the optimal dose of FUS. At the optimal dose, permeability increased by ~14-fold after 5 minutes post-FUS, and permeability returned to the control level after 25 minutes. FUS without MBs or MBs injected without FUS did not change the permeability. Our method provides an accurate in vivo assessment for the transient BBB permeability change under the treatment of FUS. The optimal FUS dose found for the reversible BBB permeability increase without BBB disruption is reliable and can be applied to future clinical trials. Keywords: antibody delivery, multiphoton microscopy, in vivo cerebral microvessel permeability, rat brain